ARTIFICIAL INTELLIGENCE TO MASTER ENGLISH LISTENING SKILLS FOR NON-ENGLISH MAJOR STUDENTS - Suryana, Irfan; Asrianto, Asrianto; Murwantono, Didik (UNDIKMA Mataram (Eks. IKIP Mataram), 2020)
Technology plays an important role in people?s day-to-day life and various aspects of life including education also use technology. Artificial Intelligence is regarded as an example of the advancement of technology. The purpose of this study is to investigate students? perceptions of using Artificial Intelligence mobile applications to improve English listening skills. It was under phenomenological qualitative research characterized by an interdisciplinary approach, mainly education and technology. The online interview was used to gain information from students? on the specific theme of artificial intelligence mobile applications in improving English listening skills. The survey consists of seven questions which become category such as 1. The Knowledge of Artificial Intelligence; 2. The Knowledge of Tune In, Joox Music, VOA Learning English Listening every day, and Netflix; 3. The Use of the Applications; 4. The Reason to Use the Applications; 5. The Use of Applications in Improving English listening Skills; 6. The Influence of the Applications toward The Users; 7. The Most Effective and Efficient Applications to Improve English Listening Skills. This survey was conducted at the Faculty of Psychology in Universitas Sarjanawiyata took part in this study. Participants were three females and two males. The results showed that the most effective and efficient Artificial Intelligence mobile application to improve English listening skills is Netflix.